Evolution of media frames about e-cigarettes from 2004 to 2019: a content analysis of newspapers in China. Issue 4 (17th May 2021) - Lyu, Joanne Chen; Wang, Di; Mao, Zhifei; Ling, Pamela M
Abstract: This study conducted a content analysis of 639 news articles about e-cigarettes in China from 2004–2019 to examine longitudinal changes in media frames and media tones about e-cigarettes in Chinese newspapers. Results indicated that policy frame was the most frequently used frame, followed by human impact frame, information frame, and uncertainty frame. Dividing the time period of 2004–2019 into four phases (i.e., 2004–2006, 2007–2010, 2011–2017 and 2018–2019), the study found that the frequency of the information frame significantly decreased over time, while the policy frame and uncertainty frame significantly increased, with the policy frame being the dominant frame in recent years. In contrast, the use of the economic frame and morality frame fluctuated, both reaching peaks in the phase of 2007–2010 and decreasing in the most recent phase. Overall, the tone of the large majority of news articles was unfavorable, and the turning point occurred in the phase of 2007–2010 when the percentage of news articles with negative tone exceeded those with positive tone for the first time. Framing of e-cigarette news articles in China demonstrated the pivotal role of policy makers in defining the e-cigarette issue, and the influence of the international public health community, as an important and reliable information source, on defining the health risk of e-cigarettes, which has implication for not only e-cigarette control, but tobacco control in China in general.